Pouched rats as detectors of tuberculosis: comparison to concentrated smear microscopy. Issue 2 (10th June 2016) - Edwards, Timothy L.; Valverde, Emilio; Mulder, Christiaan; Cox, Christophe; Poling, Alan
In 2014, 1.5 million people died of tuberculosis (TB), a disease that can be cured in nearly every case if detected in time. Rapid and accurate detection of TB is a crucial component of the World Health Organization's 2016–2035 End TB Strategy [1]. Pouched rats, Cricetomys ansorgei (previously called Cricetomys gambianus [2]), are able to detect Mycobacterium tuberculosis by sniffing sputum samples [3]. Since 2007, they have been used for second-line screening of sputum samples previously evaluated by Ziehl–Neelsen microscopy (ZN) at clinics in Tanzania. Use of the rats increases new case detections by ∼40% [3]. Pouched rats find 60% of TB patients that are missed by clinics but identifiable with concentrated smear microscopy http://ow.ly/jnUr300i2I7